Pengaruh Mata Kuliah Praktik Kewirausahaan, Persepsi Risiko, dan Lingkungan Keluarga terhadap Minat Berwirausaha Mahasiswa Prodi Kependidikan di FEB UNESA - Lusiana Wulandari; Renny Dwijayanti (Lembaga Pengembangan Kinerja Dosen, 2025)
The high unemployment rate and low entrepreneurial interest among graduates of the educational program at the Faculty of Economics and Business, Unesa, is a concerning issue. According to the Tracer Study data from the educational program, only a small percentage of graduates choose entrepreneurship. The statistics show that 15% of business education graduates, 23% of office administration education graduates, and only 3% of economics education graduates choose to become entrepreneurs. This indicates a lack of interest in entrepreneurship among educational program students. This study aims to analyze the influence of entrepreneurship practice courses, risk perception, and family environment on entrepreneurial interest among students of the educational program at the Faculty of Economics and Business, Unesa. The study employs a quantitative approach with data analysis techniques using SPSS version 25. The sample consists of 148 undergraduate students from the 2021 cohort of the educational program who have taken the entrepreneurship practice course. The findings indicate that the entrepreneurship practice course, risk perception, and family environment have a significant partial influence on entrepreneurial interest. Simultaneously, these three independent variables significantly contribute to entrepreneurial interest among students, accounting for 85.6%, while the remaining 14.4% is influenced by other factors not covered in this study. This research provides important insights into how academic factors, risk perception, and support from the family environment can affect students' entrepreneurial interest. It is expected that the findings can contribute to enhancing students' understanding and skills in entrepreneurship, making them more prepared to enter the entrepreneurial world after graduation. Ultimately, the results of this study can help increase the number of entrepreneurs in Indonesia, which will help reduce unemployment rates and strengthen the economy.